2022
DOI: 10.3389/fneur.2022.837844
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Neuronal Intranuclear Inclusion Disease Presenting With Recurrent Migraine-Like Attacks and Cerebral Edema: A Mimicker of MELAS

Abstract: BackgroundNeuronal intranuclear inclusion disease (NIID) is a progressive neurodegenerative disease associated with the GGC repeats in the 5'-untranslated region (5'UTR) of NOTCH2NLC. NIID exhibits a wide range of clinical manifestations. However, patients presenting with recurrent migraine-like attacks and cerebral edema have only rarely been reported.Case PresentationA Chinese female suffered probable migraines with aura for 10 years. At age of 51, aggravating migraine-like attacks co-occurred with a sudden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The sensory episodes in the present case were distinct from previously reported paroxysmal phenotype which usually involves diffused cortical lesions with unconsciousness, hemiplegia, aphasia, or epileptic seizures (6)(7)(8)(9). Related hyperintensity, edematous areas, and perfusion alterations in the brain imaging have been reported to characterize those typical encephalitic attacks (3).…”
Section: Discussionsupporting
confidence: 40%
“…The sensory episodes in the present case were distinct from previously reported paroxysmal phenotype which usually involves diffused cortical lesions with unconsciousness, hemiplegia, aphasia, or epileptic seizures (6)(7)(8)(9). Related hyperintensity, edematous areas, and perfusion alterations in the brain imaging have been reported to characterize those typical encephalitic attacks (3).…”
Section: Discussionsupporting
confidence: 40%
“…2,5 In the differential diagnosis of the MELAS syndrome, clinicians should exclude cerebrovascular disease, encephalitis, central nervous system demyelinating diseases, and neuronal intranuclear inclusion disease. 4,6 In addition, differentiation among different subtypes of mitochondrial diseases, such as Leigh syndrome, should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several studies have indicated that carriers with more than 300 repeats of expanded CGG show a mild or asymptomatic phenotype [ 20 , 127 ]. Beyond NIID, expanded CGG repeats in NOTCH2NLC are occasionally related to a small proportion of Parkinson's disease (PD) [ 65 , 97 , 110 ], multiple system atrophy (MSA) [ 29 ], essential tremor (ET) [ 105 ], degenerative dementia [ 4 , 101 ], ALS [ 46 , 130 ], inherited peripheral neuropathy [ 118 ], distal motor neuropathy [ 122 , 128 ], mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS) [ 57 , 123 ], and oculopharyngodistal myopathy (OPDM) [ 127 ]. Intriguingly, CGG expansion in NOTCH2NLC was rarely detected in NIID cases reported in people of Caucasian descent, suggesting that NIID is likely to be genetically heterogeneous among different ethnic groups [ 15 ].…”
Section: Polyglycine(g) Disordersmentioning
confidence: 99%